2023
DOI: 10.1113/jp285362
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue homeostasis orchestrates the oxidative, energetic, metabolic and endocrine disruption induced by binge drinking in adolescent rats

Inés Romero‐Herrera,
Fátima Nogales,
María del Carmen Gallego‐López
et al.

Abstract: Binge drinking (BD) is the most common alcohol consumption model for adolescents, and has recently been related to the generation of high oxidation and insulin resistance (IR). White adipose tissue (WAT) is a target organ for insulin action that regulates whole‐body metabolism by secreting adipokines. The present study aimed to analyse the oxidative, inflammatory, energetic and endocrine profile in the WAT of BD‐exposed adolescent rats, to obtain an integrative view of insulin secretion and WAT in IR progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…6G). In a previous recent paper, 8 we confirmed that BD exposure during adolescence led to hyperglycemia and hyperinsulinemia, which were compatible with a general IR process.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…6G). In a previous recent paper, 8 we confirmed that BD exposure during adolescence led to hyperglycemia and hyperinsulinemia, which were compatible with a general IR process.…”
Section: Discussionsupporting
confidence: 87%
“…1 Therefore, addictive disorders related to substances and/or behaviors typically begin during adolescence or early adulthood. 2 Besides, this age group is especially susceptible to the toxicity of ethanol (EtOH); 3–8 in this context, binge drinking (BD) is a pattern of acute EtOH consumption that has lately been prominently favored by teenagers, 9,10 consisting of reaching a blood alcohol concentration of 0.08% or higher within 2 hours. 11 The harmfulness of BD resides in its pronounced pro-oxidant effect on DNA, proteins and lipids, as it greatly induces the hepatic activity of cytochrome P450 2E1 (CYP2E1), much more than chronic alcoholism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of superoxide dismutase (SOD), catalase (CAT), and GPx was assayed in WAT homogenates following the methods previously described [ 29 ]. GPx activity (mU/mg protein) was determined by measuring the decrease in absorbance at 340 nm caused by nicotinamide adenine dinucleotide phosphate (NADPH) oxidation [ 30 ].…”
Section: Methodsmentioning
confidence: 99%